2018
DOI: 10.1186/s12885-018-4601-5
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR-based circulating microRNA detection serve as a promising diagnostic method for gastric cancer

Abstract: BackgroundNovel non-invasive biomarkers for gastric cancer (GC) are needed, because the present diagnostic methods for GC are either invasive or insensitive and non-specific in clinic. The presence of stable circulating microRNAs (miRNAs) in plasma suggested a promising role as GC biomarkers.MethodsBased on the quantitative droplet digital PCR (ddPCR), four miRNAs (miR-21, miR-93, miR-106a and miR-106b) related to the presence of GC were identified in plasma from a training cohort of 147 participants and a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…For example, Zhou et al clarified that a 6-miRNA signature had the potential to be used to diagnose patients with esophageal squamous cell carcinoma [ 15 ]. Moreover, Zhao et al clarified that a 4-miRNA signature could be used for the diagnosis of gastric cancer [ 16 ]. In our study, we focused on the diagnosis of STAD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhou et al clarified that a 6-miRNA signature had the potential to be used to diagnose patients with esophageal squamous cell carcinoma [ 15 ]. Moreover, Zhao et al clarified that a 4-miRNA signature could be used for the diagnosis of gastric cancer [ 16 ]. In our study, we focused on the diagnosis of STAD.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Specific miRNAs in blood or tissue samples could serve as novel biomarkers, and detection of these could contribute to cancer diagnosis and clinical outcome prediction. [21][22][23] In the current research, we analyzed the expression of miR-602 in ESCC tumors compared with that in the corresponding non-cancerous esophageal tissues. It is the first time to identify miR-602 expression in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present study examined the association between ex-miR-21 and ex-miR-92a levels and clinicopathological characteristics, and revealed that high ex-miR-21 expression was significantly associated with tumor stage. Zhao et al (34) reported a significant association between plasma miR-21 levels and tumor size, lymph node metastasis and progression of tumor stage. The present study failed to observe any association between ex-miR-92a expression and clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%